Influence of mud residues on solvent induced crystalized polycarbonate surface used as PV protective cover. (February 2016) - Yilbas, B.S.; Ali, H.; Al-Aqeeli, N.; Abu-Dheir, N.; Khaled, M.
Highlights: Crystalized polycarbonate surface has hierarchal texture and increases hydrophobicity. Adhesion between dry mud and crystalized polycarbonate surface increases considerably after dust solution dries. Dry mud residues lowers surface hydrophobicity considerably and enhances friction coefficient. Surface crystallization lowers transmittance of polycarbonate wafer. Mud residues further lowers transmittance of crystalized polycarbonate surface. Abstract: Polycarbonate wafers are used as protective cover for photovoltaic (PV) panels. Solvent crystallization of polycarbonate surface results in micro/nano spherulites and fibrils at the surface, which improve significantly surface hydrophobicity and self-cleaning characteristics of crystalized surface. Dust accumulation and mud formation on crystalized polycarbonate surface is critical for the performance of PV panels and it needs to be examined thoroughly. In the present study, experimental investigation of mud formed from the dust particles on crystalized polycarbonate surface is carried out to resemble the actual humid environments. The dry mud after effects on surface texture, hydrophobic, and optical transmission characteristics of crystalized polycarbonate surface are examined. Adhesion between the dry mud and crystalized surface are assessed and friction coefficient between the dry mud and crystalized surface is measured. It is found that crystalized polycarbonate surface has superior hydrophobic characteristics; however, mud residues at the surface cover micro/nano texture and lower surface hydrophobicity. Mud residues, remained at crystalized surface after water cleaning, increase friction coefficient and scratch hardness of the surface. In addition, mud residues lower optical transmittance of crystalized polycarbonate wafers.